A20 PREDICTORS OF PATIENT RELUCTANCE TO USE SPLIT DOSE BOWEL PREPARATION FOR EARLY MORNING COLONOSCOPIES. (1st March 2018) - Shafer, L; Waldman, C; Walker, J R; Michaud, V; Bernstein, C N; Hathout, L; Park, J; Sisler, J; Restall, G; Wittmeier, K; Singh, H
Abstract: Background: European and North American guidelines strongly recommend use of split-dose bowel preparation (SDBP) for all colonoscopies based on evidence from meta-analyses. Interviews and focus groups with endoscopists indicate some reluctance to use SDBP for early morning colonoscopies because they believe patients will not agree to it. Aims: We assessed colonoscopy patients' opinions about getting up very early in the morning to take a SDBP. Methods: self-administered anonymous survey was distributed between August 2015 to June 2016 to patients immediately prior to their outpatient colonoscopy in 6 hospitals and 2 ambulatory care centers in Winnipeg, Canada. Multinomial multivariate logistic regression analysis was performed to determine predictors of reluctance to early morning SDBP. Results: Of the 1336 respondents (52% females, median age 57 years), 33% had used SDBP and overall 13.5% did not complete the entire recommended laxative intake. 49% of survey respondents were willing or very willing to do early am SDBP, 24% were neutral and 27% reluctant or very reluctant. When the outcome of reluctance was compared to willing, the predictors of reluctance on multivariate analysis included more than one prior colonoscopy (OR 1.60; 95% CI: 1.04–2.47), female gender (OR 1.81; 95% CI: 1.29–2.54), lack of clear information (OR: 4.40 95% CI: 2.08–9.28), high level of anxiety for bowel preparation (score > 80 on a 0–100 scale) (OR 1.79 95% CI: 1.02–3.14), and type of laxative used (4 litres PEG alone vs. sodium picosulfalte with adjunct agent: OR 1.60 95% CI: 1.01–2.53). There was no effect of procedure time of day, indication for colonoscopy or level of education. There was an interaction effect between use of SDBP and finishing the laxative intake. Among those who finished the laxative, use of day before preparation was associated with a more than 2-fold greater reluctance to use SDBP for future colonoscopy (OR 2.24 95% CI: 1.43–3.51). The same predictors were identified when reluctance was compared to willing and neutral combined. Conclusions: In spite of clear evidence of superior efficacy of SDBP, there continues to be limited use of SDBP in usual clinical practice. However, only a minority of patients expressed reluctance to get up early for SDBP. Efforts to clearly inform patients about the advantages of SDBP and arrangements to move the most reluctant to later morning appointments may support increased SDBP use. Funding Agencies: Research Manitoba